If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + 2 = -6 Reorder the terms: 2 + 1x = -6 Solving 2 + 1x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 1x = -6 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = -6 + -2 1x = -6 + -2 Combine like terms: -6 + -2 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| -4x^2=9x | | 5a+3(216+a)=888 | | 4y-7-6y-2= | | -2-2(-7x+7)=82 | | -15=-12+3r | | -7(1k-8)+2k= | | 2.5x+4=6x+4 | | 5x+5=6x+2 | | (c+3)(c+4)=2 | | 7x+3=-2x+21 | | Mp+mz=r | | lnx^7-10lnx=1 | | 3+2*[(2+1)*5+8]= | | -5x+2=-2x-31 | | 2y+6+8y+10+y+32=180 | | X^2+13x-64=0 | | 5m-28=-33+6m | | 3x^2+56=-136 | | 9n-23=17+n | | 2y^2-4y-8=y^2+y | | (1.8X+0)-(1.4X+0.6)= | | 2(x+4)-126=0 | | 3+y=10+3 | | m^2+m+.25=0 | | p+12=24 | | (5-4x)(x-5)=0 | | 12x^2-52x+48=0 | | ln(11x-7)=0 | | 3y-8y=12 | | 6x+5=54-x | | 0.2x+0.01=0.2y | | 20%-39.99= |